Role of standardized grape polyphenol preparation as a novel treatment to improve synaptic plasticity through attenuation of features of metabolic syndrome in a mouse model. Issue 12 (21st August 2013) - Wang, Jun; Tang, Cheuk; Ferruzzi, Mario G.; Gong, Bing; Song, Brian J.; Janle, Elsa M.; Chen, Tzu‐Ying; Cooper, Bruce; Varghese, Merina; Cheng, Alice; Freire, Daniel; Bilski, Amanda; et al.
<x xml:space="preserve">Abstract</x> Scope Metabolic syndrome has become an epidemic and poses tremendous burden on the health system. People with metabolic syndrome are more likely to experience cognitive decline. As obesity and sedentary lifestyles become more common, the development of early prevention strategies is critical. In this study, we explore the potential beneficial effects of a combinatory polyphenol preparation composed of grape seed extract, Concord purple grape juice extract, and resveratrol, referred to as standardized grape polyphenol preparation (SGP), on peripheral as well as brain dysfunction induced by metabolic syndrome. Methods and results We found dietary fat content had minimal effect on absorption of metabolites of major polyphenols derived from SGP. Using a diet‐induced animal model of metabolic syndrome (DIM), we found that brain functional connectivity and synaptic plasticity are compromised in the DIM mice. Treatment with SGP not only prevented peripheral metabolic abnormality but also improved brain synaptic plasticity. Conclusion Our study demonstrated that SGP, comprised of multiple bioavailable and bioactive components targeting a wide range of metabolic syndrome related pathological features, provides greater global protection against peripheral and central nervous system dysfunctions and can be potentially developed as a novel prevention/treatment for improving brain connectivity and synaptic plasticity important for learning and memory.